EKSPLORASI POTENSI DESA WISATA BERBASIS KEMARITIMAN DI DESA TAPULAGA KCAMATAN SOROPIA KABUPATEN KONAWE - Ridwan, Harnina; Iba, La; Sumule Genggong, Marsia; Jaya, Asrul; Sarpin, Sarpin; Herman, La Ode; Juhaepa, Juhaepa; Masrul, Masrul; Muhammad Umran, La Ode; Sirajuddin, Sirajuddin (Universitas Halu Oleo, 2023)
Community participation in maintaining the natural and cultural resources they own is a big contribution and has the potential to become a tourist attraction, including for communities in coastal areas. The development of tourism in the coastal area of Soropia District, Konawe Regency has not shown maximum results so it has no impact on increasing people's income in the area. One of the main components in tourism communication is human resources, especially in tourism activities related to community care and community welfare. The growth and development of community participation in tourism is largely determined by three main elements, namely, the opportunity given to the community to participate in tourism, the community's willingness to participate in tourism development, and the community's ability to participate in tourism progress. Solution offered: Providing education and stimulating public sensitivity to the benefits of maritime tourism in the coastal area of Tapulaga Village. Fundamental contribution to the target audience. Formation of understanding of village officials, tourism business actors, tourism workers and local communities in the coastal area of Tapulaga Village in exploring maritime tourism development.